Cyber security and threats concepts, methodologies, tools, and applications (Information Science Reference, 2018)
"This book contains a compendium of the latest academic material on new methodologies and applications in the areas of digital security and threats. Including innovative studies on cloud security, online threat protection, and cryptography"--